BIBLIOMETRIC ANALYSIS AND MAPPING: TREND OF ‘ LEARNING METHOD” IN 2012-2022 - Elihami; Mohd. Melbourne (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This article analyzes the systematic process of the learning method. The research in this article begins with the search for articles through the keyword of learning method based on the Scopus database in 2012-2022, which consisted of 130 articles. The research uses descriptive analysis and VOSviewer software-assisted visualized data. The analysis results indicate that the three dominant concepts that are mostly studied are learning method, learning, and method. The research indicates the development and urgency of the learning method. Meanwhile, the limitation is that the articles reviewed were only sourced from Scopus. Hence, it is recommended by the researchers for further research using an approach of comparative analysis by implementing the Web of Science (WoS) database and increasing the length of the search period for the latest articles, especially for the learning method.